Hubungan Tingkat Pendidikan, Pengetahuan dan Sikap Masyarakat dengan Perilaku Hidup Bersih dan Sehat di Wilayah Kerja Puskesmas Poasia Kota Kendari - Amiruddin, Amiruddin; Suama, I Wayan; Munir, Asmawati; Nurhidayah, Dwi; Rahayu, Karina Dwi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
The phenomenon of clean and healthy living behavior (PHBS) among the community is very worrying, many factors influence PHBS such as level of education, knowledge and attitudes. This study aims to determine the relationship between the level of education, knowledge and attitudes with PHBS in the working area of the Poasia Health Center. The population of this study is the total number of families of 7,165 families. The sampling technique was Proportional Cluster Random Sampling so that a total of 379 respondents were obtained. The data collection technique was carried out by analytic observation through a cross sectional approach. The data analysis technique uses the Spearman Rank correlation coefficient test. The results showed that the level of education in the high category was 182 (48.0%) respondents, the middle category was 177 (46.7%) respondents, the low category was 20 (2.3%) respondents and the level of knowledge in the high category was 346 (91.3%). %) respondents, medium category 24 (6.3%) respondents, low category 9 (2.4%) respondents, and good attitude category 356 (93.9%) respondents and medium category 23 (6.0%) respondents . Statistical test results show that education level is related to clean and healthy living behavior (ρ <0.05), knowledge level is related to clean and healthy living behavior (ρ <0.05), attitude is related to clean and healthy living behavior (ρ < 0.05).